Model Kolaboratif dalam Tata Kelola Pemerintahan - Mukhlis Fataruba (Jurnal Ilmu Sosial dan Humaniora, 2025)
Collaborative governance is an approach gaining increasing attention in the context of public administration. This approach emphasizes the involvement of various stakeholders in the decision-making process to achieve more inclusive and effective outcomes. This article explores the concept, principles, and implementation of the collaborative governance model, along with its benefits and challenges. This research aims to provide a deeper understanding of the importance of multi-actor participation in public policy management. In the collaborative governance model, the main principles applied include inclusivity, active participation, transparency, accountability, and consensus. Inclusivity ensures that all relevant stakeholders are involved in decision-making. Active participation encourages significant contributions from all parties involved, while transparency ensures openness in decision-making processes and outcomes. Accountability maintains accountability for actions taken, and consensus helps reach agreements through constructive dialogue. Implementing the collaborative governance model involves several important steps, such as stakeholder identification, facilitating dialogue and communication, policy formulation, consensus-based decision-making, and policy implementation and monitoring. Each step aims to build structures and mechanisms that support active participation and collaboration among stakeholders. Case studies from various countries, including Indonesia's "Desa Mandiri" program, illustrate how collaboration can improve effectiveness and accountability in local resource management. While collaborative governance offers various benefits, such as increased legitimacy, better decision-making quality, and more efficient resource utilization, challenges such as coordination complexity, capacity gaps, and potential conflict require careful management. In conclusion, to achieve success in this model, it is crucial for all parties to commit to the principles of collaboration and openness, thus creating better governance that is responsive to community needs